Analysis Of The Central Role Of Beach Tourism Objects In Village Economic Development: A Case Study Of Tanjung Bias Beach, West Lombok - Ayu, Dyah Ayu Setyaningrum; Diswandi (Faculty of Economics and Business, University of Mataram, 2023)
The purpose of this study was to analyze the role of tourist attractions in the economic development of the village, taking the case at Tanjung Bias Beach, Senteluk Village, Batu Layar District, West Lombok Regency. This research uses a qualitative approach with descriptive methods. The data collection techniques used were observation, interviews, and documentation. The determination of informants in this study used purposive and snowball sampling. The data validity method used is the triangulation method. Based on the results of the research that has been done, it can be seen that the role of Tanjung Bias Beach tourist attraction is very influential in the economic development of Senteluk Village. There are three roles that help improve the economic development of the village, namely opening business opportunities, increasing community income, and creating jobs.